Does PmatE help students to be more autonomous in the learning of mathematical subjects at university level? - Pais Sónia
Since 1989, the Mathematics Education Project (PmatE – Projecto Matemática Ensino) has developed several strategies to increase the interest and improve the success of students in Mathematics. PmatE developed a platform of computer aided education (PCA), currently available only in the internet, including all grades since primary school. The main goal of this platform is to support teaching, being a tool that allows: the management of the groups involved; the elaboration of tests; the research of student performance; the analysis of results and other functionalities of management. The developed programs are a tool to support education, evaluation and learning. However, this platform has not yet been subject to a systematic evaluation, especially at the superior education level, that will allow us to conclude whether its goals have been achieved. From this standpoint, we develop a case study with Science Food Engineering students. In this article, we discuss the resonance of the platform of computer aided education (PCA) developed for the PmatE in terms of the autonomy skills development. This paper describes how it is conceived as well as the main results. We concluded that, although recognized the platform potential, a considerable number of students preferred a more traditional approach.